Coastal management lines as a key tool to promote integrated coastal management : a comparative review of South Africa's emerging legal framework with that of selected Euro-Mediterranean countries - Pienaar, Alecia (Institute of Marine and Environmental Law, 2016)
The coastal zone represents an endemic ecosystem of geomorphic complexity, characterised by its dynamic state of transition and increasing sensitivity. It is widely acknowledged that the environmental complexities and distinctiveness of this area is an attribute matched only be its attractiveness for human settlement and resource utilisation. Viewed through an environmental lens, the proliferation of urban coastal development is, however, diminishing coastal resilience to an extent that is both unsustainable and injudicious. In this context, proper management of the coastal zone necessitates the application of integrated land use planning mechanisms responsive not only to the ecological dynamics of a land-sea interface, but also to the increasing pressures of human use and development activities. This dissertation identified set-back lines or coastal management lines (CMLs) as a regulatory mechanism that essentially conforms to such criterion. South Africa is currently experimenting with implementing the provisions in the National Environmental Management: Integrated Coastal Management Act 24 of 2008 (NEMICMA), which provides for CMLs as a key tool for promoting integrated coastal management. The aim of this dissertation was to critically review the domestic legal framework and experience to date in implementing this scheme. Owing to the novelty of CMLs in the South African jurisdiction, a reference point or legal backdrop was necessary to critically evaluate the peculiarities and potential of the NEMICMA framework. For this reason, this dissertation undertook a critical and comparative study on the regulation of CMLs in both South Africa and selected Euro- Mediterranean states, namely France, Spain and Greece.